Cytotoxic phenolic glycosides from the seeds of Senna tora. (October 2021) - Hanh, Tran Thi Hong; Anh, Le Ngoc; Trung, Nguyen Quang; Quang, Tran Hong; Anh, Do Hoang; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Van Minh, Chau
Graphical abstract: Highlights: Fourteen glycoside derivatives were isolated from Senna tora seeds. Three new compounds (1 –3 ) were elucidated by NMR, CD, and HR-ESI-QTOF mass spectra. Their cytotoxicity against three human cancer cell lines was evaluated by SRB assay. Abstract: Phytochemical investigations of Senna tora seeds led to the isolation of fourteen phenolic glycosides, including three new compounds, namely, sennatorosides A–C (1 –3 ). The chemical structures of the isolated compounds were confirmed by a detailed analysis of the 1D and 2D NMR, HR-ESI-QTOF mass, and ECD spectra. Among the isolated compounds, 1-[(1-(<β>-d -glucopyranosyl)oxy-8-hydroxy-methoxynaphthalen)-6-yl]propan-2-one (11 ) exhibited strong cytotoxic activity against three tested cancer cell lines, SK-LU-1 (lung cancer), HepG2 (hepatoma cancer), and MCF-7 (breast cancer), with IC50 values of 8.05 ± 0.28, 9.52 ± 1.20, and 8.54 ± 0.85 μM, respectively, whereas compounds 1 –4, 6 –9, 12, and 14 revealed moderated or weak cytotoxicity, with IC50 values ranging from 44.59 ± 5.03–98.24 ± 2.45 μM.